1998
DOI: 10.1016/s1059-1311(05)80005-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical courses of pure sleep epilepsies

Abstract: This study aims to understand seizure control outcomes and the risk of developing new wake seizures (WS) related to the different types of pure sleep epilepsies (SE), which is important in making rational management plans. A retrospective review of the Yonsei Epilepsy Clinic Registry identified 63 patients with pure SE not belonging to any specific epileptic syndromes. They were divided into the group of generalized tonic-clonic seizures during sleep (S-GTCS : n = 21) and the group of partial epilepsies during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
2
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 17 publications
0
25
2
3
Order By: Relevance
“…D'Alessandro et al's 20 paper from 1983 was more a description of outcomes from their practice than a robust study and was not considered further. Park et al's 21 retrospective single centre study identified 63 people with pure sleep-related epilepsy and 12 of whom developed awake seizures within the 2 years of study. Provini et al's 25 retrospective review of ‘nocturnal’ frontal-lobe epilepsy was performed at a tertiary centre in Italy solely including people referred for polysomnography.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…D'Alessandro et al's 20 paper from 1983 was more a description of outcomes from their practice than a robust study and was not considered further. Park et al's 21 retrospective single centre study identified 63 people with pure sleep-related epilepsy and 12 of whom developed awake seizures within the 2 years of study. Provini et al's 25 retrospective review of ‘nocturnal’ frontal-lobe epilepsy was performed at a tertiary centre in Italy solely including people referred for polysomnography.…”
Section: Resultsmentioning
confidence: 99%
“…However, there was shared speculation that focal onset seizures would be poorly described by a bed partner. Park et al's 21 paper identified a discrepancy between focal and generalised epilepsies. Eleven out of 42 (26%) developed awake seizures in the partial-onset group, and the single individual in the generalised-onset epilepsy (1/21, 5%) experienced a likely focal event.…”
Section: Resultsmentioning
confidence: 99%
“…3,4 Uy kunun in te rik tal epi lep ti form bo şa lım lar (IED) üze-rin de ve ba zı epi lep tik nö bet ler de di rek et ki si ol du ğu bi lin mek te dir. [2][3][4][5][6][7] Bu ça lış ma da epi lep tik nö bet le rin uy ku/uyanık lık rit mi ile or ta ya çı kış özel lik le ri ya nı sı ra klinik, elek tro fiz yo lo jik ve rad yo lo jik ve ri ler ile bir lik te li ği ir de len mek is ten di.…”
unclassified
“…uy ku da KSP nö bet le ri göz le nen has ta la rın uya nık lık ta da nö bet ge çir me risk le ri nin da ha faz la ol du ğu nu, ay rı ca prog noz la rı nın nok tür nal epi lep tik nö bet ge çi ren has ta la ra gö re da ha kö tü ol du ğu nu sap ta mış lar dır. 7 Bu has ta la rın an ti e pi lep tik ilaç la ra ya nıt lı lı ğı nın da da ha az ol du ğu bil di ril miş tir. 7 Ben zer şekil de bi zim ça lış ma mız da da KSP nö bet özel li ğin de epi lep tik nö bet le ri olan ol gu la rın %43.9'un da (n= 118) nö-bet le rin kıs mi ola rak kon trol al tı na alı na bil di ği göz len miş tir.…”
unclassified
See 1 more Smart Citation